The Applied Linguistics Aspects of Using Digital Media: Analysis of Women's Instagram Account Captions Based on Language Style. - Farida, Ana Lutfiana; Dzulfikri, Dzulfikri; Mistar, Junaidi (Universitas Cokroaminoto Palopo, 2023)
This study discusses the Applied Linguistics Aspects of Using Digital Media: Analysis of Women's Instagram Account Captions Based on Language Style. The researcher used Chaika's theory in 1982 about five styles of language in the form of formality; formal style, informal style, colloquial style, casual style and intimate style. Along with the development of the social media phenomenon which provides unlimited aspects for young people, especially women. In this study, it aims to provide an overview of the style of language used by women when making a caption on Instagram. As of Mei 2023, there are several women accounts that have the highest number of followers, one of which was chosen by the researcher to be used as material for analysis to create texts with different language styles. The researcher chose five women accounts, namely Selena Gomez, Kylie Jenner, Ariana Grande, Kim Kardashian, and Taylor Swift. In this case, the researcher only took one post along with the caption from each account. This study uses descriptive qualitative research because it processes words by analyzing and describing issues related to social aspects of phenomena in social media. The result is five posts from Instagram captions were obtained according to the type and characteristics of the language style. Language experts classify language styles into several types, one of which is formal style, informal style, colloquial style, casual style, and intimate style. Keywords–Instagram caption; women’s account, language style